Death incidents following transcatheter edge-to-edge repair (TEER) with the MitraClip device: analysis of 10-years post-marketing death reports from the Manufacturer and User Facility Device Experience (MAUDE) registry - Xinghe Sun; Yifei Zhao; Yan Li (BMC Cardiovascular Disorders)
Abstract Background The transcatheter edge-to-edge repair (TEER) technique, facilitated by the MitraClip device, is a minimally invasive intervention designed for high-risk patients with mitral regurgitation (MR). This study conducts a retrospective analysis of death events associated with MitraClip implantation over a ten-year decade, utilizing data from the FDA’s Manufacturer and User Facility Device Experience (MAUDE) database to evaluate trends in safety outcomes. Methods A comprehensive search of the publicly accessible MAUDE database was conducted to retrieve reports of deaths and injuries related to MitraClip implantation from October 2013 to September 2023. Duplicate reports and records from unrelated sources were excluded. The Cochran-Armitage test was performed to evaluate trends in the proportion of fatal events over time. Results During the 10-year period following FDA approval, the MAUDE database recorded a total of 927 death reports and 9,211 injury reports associated with MitraClip. After excluding duplicates and irrelevant reports, 592 death cases were analyzed. The most commonly reported complications were MR (26.69%), tissue damage (24.16%), and hypotension (22.13%). The most frequent device-related issues were incomplete coaptation (14.70%), difficulty removing the divice (6.42%), and failure to adhere or bond/positioning failure(4.90%). Notably, 76.94% of deaths occurred within one year of implantation. The proportion of fatal events demonstrated a gradual decline, from 15.9% in 2014–2015 to 3.5% in 2020–2021 (p < 0.0001). Conclusions This analysis of the MAUDE database indicates a gradual decline in the proportion of fatal events associated with MitraClip implantation, which may be attributed to growing operator experience and advancements in device design. Nonetheless, persistent focus is required on managing complications and addressing potential risks to further enhance device performance and optimize its clinical utility.